Green Open Space Analysis with Utilization Remote Sensing and Geographical Information System in Banda Aceh City - Mice Putri Afriyani; Wido Iskandar; Syahrul Ridha; Muttakin Muttakin (Universitas Pendidikan Ganesha, 2023)
Banda Aceh City, the capital of Aceh Province, has experienced both urban development and an increase in population. The increase in the physical development of the city in the form of the construction of residential areas, transportation facilities, trade, industry, and other services has resulted in an increase in the transfer of land from open space to built-up space, which in turn has an impact on reducing green open space (RTH). The purpose of this research is to determine whether the city of Banda Aceh has fulfilled the status of a city with sufficient green open space of 30% of the total area of ​​Banda Aceh city if studied through remote sensing. This study aimed to analyze the green open spaces of Banda Aceh City based on remote sensing and Geographic Information Systems. The scope of this research is the entire district of Banda Aceh City. The proportion of Banda Aceh City that must be made into an open green area is a minimum of 1,840.89 ha (30%) with the provisions of 20% public green open space and 10% private green open space. Data processing methods and techniques use Spatial analysis with exploratory methods. Based on the results of data analysis through remote sensing. This study concludes that Banda Aceh City's green open space is currently 2,461.57 ha (41.11%), with the distribution of public green open space of 878.24 ha (14.31%) and private green open space of 1,583.32 ha (25.80%). It cannot be said that it meets the criteria for the number of green open spaces because the number of private green open spaces is greater than the number of public green open spaces.